Effectiveness of Social Media Interventions for People With Schizophrenia: A Systematic Review and Meta-Analysis - Välimäki, Maritta (J Med Internet Res, 2016)
BACKGROUND: Recent studies have shown that people with serious mental disorders spend time online for the purposes of disclosure, information gathering, or gaming. However, coherent information on the effects of social media on treatment for people with schizophrenia is still lacking. OBJECTIVE: Our aim was to determine the effects of social media interventions for supporting mental health and well-being among people with schizophrenia. METHODS: A systematic review and meta-analysis were undertaken to determine the effects of social media interventions for supporting mental health and well-being among people with schizophrenia. Ten databases were searched, while search parameters included English-only manuscripts published prior to June 25, 2015. Study appraisals were made independently by 2 reviewers, and qualitative and quantitative syntheses of data were conducted. RESULTS: Out of 1043 identified records, only two randomized studies of moderate quality (three records, total N=331, duration 12 months) met the inclusion criteria. Participants were people with schizophrenia spectrum or an affective disorder. Social media was used as part of Web-based psychoeducation, or as online peer support (listserv and bulletin board). Outcome measures included perceived stress, social support, and disease-related distress. At 3 months, participants with schizophrenia in the intervention group reported lower perceived stress levels ( P=.04) and showed a trend for a higher perceived level of social support ( P=.06). However, those who reported more positive experiences with the peer support group also reported higher levels of psychological distress ( P=.01). CONCLUSIONS: Despite using comprehensive searches from 10 databases, we found only two studies, whereas numerous reports have been published citing the benefits of social media in mental health. Findings suggest the effects of social media interventions are largely unknown. More research is needed to understand the effects of social media, for users with and without mental illness, in order to determine the impact on mental well-being ofsocial media use as well as its risks.